Micro Waqf Bank Priority Strategy Determines Business Financing Criteria - Muhamad Fauzi; Yusuf Haji-Othman; Mukhaer Pakkanna (Journal of Islamic Economics and Philanthropy, 2025)
Sharia micro business financing plays a vital philanthropic role for communities in Indonesia. Micro waqf banks facilitate access to business capital for those in need, yet research on standard recipient criteria and supporting factors remains limited. This study identifies priority strategies, key criteria, and primary supporting factors for business financing at Micro Waqf Banks in Banten Province. Employing a mixed-methods approach, we conducted case studies at El Manahij, Lan Taburo, and An Nawawi micro waqf banks. Data collection involved questionnaires and interviews with supervisors, managers, and team leaders, selected through purposive sampling. We analysed data using descriptive statistics and the Analytic Network Process (ANP) with SuperDecisions software. The results show that customer character and track record serve as the main criteria for micro waqf bank financing. Business feasibility and social support are the two most significant factors in support. These findings underscore the need to enhance character assessments and record-keeping through the digitisation of data and integrated monitoring. By doing so, micro waqf banks can enhance their effectiveness and contribute further to philanthropic micro business financing. Future research should extend the regional scope and compare financing criteria and strategies across various provinces.